Driving forces for fuelwood use in households in the Thulamela municipality, South Africa - Solomon Eghosa Uhunamure; Nthaduleni Samuel Nethengwe; Agnes Musyoki (Journal of Energy in Southern Africa, 2017)
Abstract Energy is a fundamental requirement to sustain human life, but most people in rural areas do not have enough access to efficient and affordable energy resources. Socio-economic measures are increasingly used to determine household energy consumption patterns. The pattern of household energy consumption represents the status of welfare as well as the stage of a country’s economic development. Household energy consumption is expected to increase in the future, along with growth in the economy and a rise in per capita incomes. This study was undertaken to understand the driving forces for energy preference in rural households, while reassessing the energy ladder and multiple fuel use. Two hundred questionnaires were administered to elicit information from respondents in Altein, Botsoleni, Makhovha and Thenzheni in the Thulamela municipality of South Africa. A non-parametric test (Chi-square) was used to determine the relationships amongst the factors influencing the use of fuelwood in the study area. Cramer’s V was used to test the association of the variables, the strength and the direction of the relationship. The results indicate that household income, educational level and employment status, cultural norms and values, are among the key determinants of the energy preference scale.